The glass man : a novel - De la Motte, Anders, 1971- (De la Motte, Anders, 1971- Askerserien., 2025)
Detective Leonore Asker investigates a mutilated body found on her estranged father's farm while writer Martin Hill uncovers eerie legends at a remote estate, their paths converging as a mysterious figure known as the Glass Man emerges from the shadows.